Propose Customer Development Framework for Cloud-Based Enterprise Resource Planning (ERP) Start-up - Wijaya, Marcel; Dhewanto, Wawan (School of Business and Management Institut Teknologi Bandung, 2019)
IT role in business has been enabling faster analysis and more reliable decision making and it has been the backbone for industry’s competitive factor. However, full scale ERP software are still too costly for small and medium enterprises. Company X wanted to build the disruptive integrated Business Process Management software that could be accepted by wide range of business. Putting great efforts on product development prior to launching, the founders had not probed the problems from the customer’s point of view. This research approached the Company’s problem with customer learning and discovery from Customer Development Model. The approach includes testing the hypotheses of the customer – problem – solution fit, and product – market fit by interviewing several businesses, with the Javelin Validation Board (Lean Startup Machine) was used to help the iteration of validation process. The result of the hypotheses validation includes: narrowing customer target segment, splitting the features to several modules to be sold separately, and adding customer support team. Company X needs to narrow the customer target segment to be small and medium scale enterprises which had not settled with complex system and just about to gain more control over their operations.